The add-on effects of Danhong injection among patients with ischemic stroke receiving Western medicines: A systematic review and meta-analysis - Ma, Yu; Deng, Ke; Liu, Jiali; Ma, Bin; Mei, Fan; Hui, Wen; Luo, Xiaochao; Yao, Minghong; Liu, Yanmei; Qin, Xuan; Zhou, Xu; Zou, Kang; et al. (Frontiers in Pharmacology, 2022)
Background: Danhong injection is widely used for treating ischemic stroke in China. However, its effects on ischemic stroke patients when adding to western medicines (i.e., the add-on effect) were not well established. Methods: We searched PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL) and three Chinese databases from inception to 20 July 2020 to identify randomized clinical trials (RCTs) that assessed the effects of Danhong injection as an add-on therapy in patients with ischemic stroke. Pairs of trained reviewers independently screened for eligible studies, assessed risk of bias, and extracted data. The outcomes were National Institutes of Health Stroke Scale Score (NIHSS), Barthel index, activities of daily living (ADL), total cholesterol and homocysteine (Hcy). Results: Sixty-seven RCTs of 6594 patients with varying risk of bias were included. Compared with western medicine alone, the addition of Danhong injection to western medicine significantly lowered NIHSS score (45 RCTs with 4565 patients; MD -4.21, 95% CI -4.96～-3.46), total cholesterol (10 trials with 1019 patients; MD -1.14 mmol/L, 95% CI -1.57～-0.72) and Hcy (4 trials with 392 patients; MD -3.54 μmol/L, 95% CI -4.38～-2.07). The addition of Danhong also increased Barthel index (14 trials with 1270 patients; MD 8.71, 95% CI 3.68～13.74) and ADL (12 trials with 1114 patients; MD 14.48, 95% CI 9.04～19.92) scores. Subgroup analyses showed differential effects in average cerebral blood flow rate by mean age of patients (<60 years: MD 0.74 cm/s, 95% CI 0.29～1.19; ≥60 years: MD 4.09 cm/s, 95% CI 2.02～6.16; interaction P=0.002) and NIHSS score by type of baseline western medicines (interaction P<0.00001). Conclusions: The addition of Danhong injection to western medicine may improve neurological function, self-care ability and blood lipids of ischemic stroke patients. However, given most included trials with unclear risk of bias, current evidence is not definitive, and more carefully designed and conducted trials are warranted to confirm our findings.